Fabrication of different conductive matrix supported binary metal oxides for supercapacitors applications. Issue 4 (15th February 2021) - Shaheen, Nusrat; Aadil, Muhammad; Zulfiqar, Sonia; Sabeeh, Humera; Agboola, Philips O.; Warsi, Muhammad Farooq; Aly Aboud, Mohamed F.; Shakir, Imran
Abstract: Here, we have fabricated the spinel binary-metal oxide (FeCo2 O4 ) via a solvent-free and cost-effective approach. The nanocomposites of the as-fabricated binary-metal spinel oxide have been prepared with three different conductive-matrices, namely r-GO, CNTs, and PANI, via ultra-sonication approach. The spinel phase and surface functionalities of the fabricated FeCo2 O4 sample have been confirmed via XRD and FT-IR analyses, respectively. The morphological-structure and elemental composition of the fabricated samples have been probed via FESEM and EDX results. The role of added conductive-matrices in the improvement of the electrical conductivities of the fabricated nanocomposites has been investigated via I–V experiments. The electrochemical experiments, conducted in half-cell configuration, showed that FeCo2 O4 /PANI nanocomposite exhibited the highest specific capacitance (658.9 Fg -1 ) than that of the remaining two nanocomposites. Furthermore, FeCo2 O4 /PANI nanocomposite exhibited excellent cyclic stability as it lost just 8.3% of its initial specific capacitance even after 3000 cyclic tests. The superior capacitive-activity of the FeCo2 O4 /PANI nanocomposite is accredited to its high conductivity, large surface area, and synergy effects between the pseudocapacitance derived from the PANI and FeCo2 O4 nanostructure. The electrochemical and electrical measurements suggested that FeCo2 O4 /PANI nanostructure is an emerging contender for energy storage applications.